Apocalypse Now’s Nightmare - Paché, Gilles (European Journal of Applied Sciences, 2025)
The production of Apocalypse Now serves as a compelling case study in chaos management under extreme conditions. Confronted with a host of challenges—ranging from unpredictable weather and the health issues of cast members to financial and interpersonal tensions—Francis Ford Coppola’s project offers valuable insights. Risk management was crucial, particularly the creation of contingency plans to address unforeseen events like Martin Sheen’s heart attack and a series of destructive typhoons. Logistical flow management also faced significant obstacles, as filming occurred in a remote location with limited infrastructure. Finally, Coppola’s leadership under pressure, balancing crisis management, improvisation, and team motivation, underscores the importance of organizational agility. This research note provides an analysis of these challenges and highlights their relevance across various industries.